Attitudes towards geroprotection: measuring willingness, from lifestyle changes to drug use - Brouwers, Sam J.; Janssens, Georges E.; Spiegel, Tali (Frontiers in Aging, 2024)
IntroductionGeroprotection is an emerging field of research focused on devising strategies for combating the mechanisms of ageing. This study held three aims: 1) to explore the willingness to utilise five different geroprotective measures (i.e., exercise, supplements, intermittent fasting, metformin, and rapamycin use), 2) to explore whether the willingness differs based on respondents’ sociodemographic characteristics and 3) to explore the association between trust in medical institutions and willingness to utilise different geroprotective measures.MethodsA questionnaire was used to assess the attitudes of a sample of the Dutch population by way of both convenience and snowball sampling (final N = 178). Descriptive data and bivariate correlations were used in the analyses.ResultsRelatively high social acceptance of both exercise (66%) and supplements (82%) was found, whereas intermittent fasting (30%), metformin (26%), and rapamycin (10%) were less supported. Males were significantly more likely to be open to exercise and women to supplement use. Trust in medical institutions correlated significantly with the willingness to start metformin.DiscussionExploratory research can only provide a first step in understanding the social acceptance of geroprotection measures. Nevertheless, this study clearly illustrates more well-known measures promoted by public health policy are also more accepted and used. Public health campaigns could consider the sex differences in the uptake of exercise and supplements, and future research may want to delve deeper into the role of facilitating trust relations between medical institutions and the public in promoting the use of geroprotective drugs.